2019
DOI: 10.1029/2019gl084828
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical Pacific Ocean Temperature Fluctuations in the Common Era: Multidecadal Variability and Its Relationship With Southwestern North American Megadroughts

Abstract: Variability of North Pacific sea surface temperatures (SSTs) on multidecadal timescales plays an important role in modulating global climate and regional hydroclimate. The principle modern phenomenon associated with this variability is the Pacific Decadal Oscillation (PDO); however, our understanding of the PDO and multidecadal SST variability more broadly is limited to SST observations from the historical era and land-based proxy reconstructions. Here, we reconstruct multidecadal Pacific Ocean SST variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…sen et al, 2011), or a combination of proxies (Delworth and Mann, 2000;Wang et al, 2017). Paleo-reconstructions have also been performed of the PDO (D' Arrigo et al, 2001;Mac-Donald and Case, 2005;Felis et al, 2010;O'Mara et al, 2019).…”
Section: Sea Surface Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…sen et al, 2011), or a combination of proxies (Delworth and Mann, 2000;Wang et al, 2017). Paleo-reconstructions have also been performed of the PDO (D' Arrigo et al, 2001;Mac-Donald and Case, 2005;Felis et al, 2010;O'Mara et al, 2019).…”
Section: Sea Surface Temperaturementioning
confidence: 99%
“…Large-scale SST variability is tightly coupled to the Earth's energy balance through surface heat fluxes (SHFs) which change the ocean heat content (OHC) and affect the global mean surface temperature (GMST). The SST-SHF coupling is complex: generally, anomalously high SSTs lead to a loss of heat from the oceans, but there is substantial geographic and seasonal variability depending on atmospheric conditions such as wind speed and cloud presence (Park et al, 2005). In the midlatitude North Atlantic, sub-decadal atmospheric variability drives the SHF, but low-frequency changes in SST drive the SHF on timescales longer than 10 years (Gulev et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To convert PCM00-78K depth of the sediment into calendar age, we used the stratigraphic correlation with a composite of a box and kasten cores that cover the sediment record from the surface (detailed information about stratigraphic correlation and age model can be found in the Supporting Information). The information provided by new planktic foraminifera AMS 14 C results from core PCM00-78K, and the excess 210 Pb and the peak in 137 Cs results from box core PCM00-78C (Table S2, Figure S2, see also O'Mara et al, 2019), showed conflicting results in the tie points between box and kasten cores ( Figure S1) with a previous stratigraphic correlation ( Abella-Gutiérrez & Herguera, 2016). This led us to the reinterpretation of the stratigraphic correlation based on the laminations and to change the relative position of the PCM00-78K in the composite depth to a 40-mm shallower depth than previously considered.…”
Section: Age Modelmentioning
confidence: 99%
“…Since the authors mentioned paleoclimate studies in the Atlantic, I think it won't be complete without a discussion (or at least mentioning) on paleoclimate studies in the Pacific. Examples include: D 'Arrigo et al 2001;MacDonald and Case 2005;Felis et al 2010;Lapointe 2017;O'Mara et al 2019.…”
Section: )mentioning
confidence: 99%